Monitoring distributed computing systems on the basis of the determined shortest paths and shortest hamiltonian cycles in a graph - Листровой, Сергей Владимирович; Минухин, Сергей Владимирович; Листровая, Елена Сергеевна (Eastern-European Journal of Enterprise Technologies, 2015)
The tasks of monitoring the Distributed Computing System (DCS) are associated with optimization of the order (sequence) of surveying the monitored objects, such as resources (clusters and cluster nodes), carried out tasks (downloads), communication channels, and database servers. The problems are solved due to the use of plug-ins that include programs to initialize the startup and operation of remote services (agents), while the latter provide control over the DCS performance. Since the size of each of the transmitted commands to initialize the remote services of the monitored objects is several kilobytes and there are thousands of the DCS-controlled nodes, the volume of the transmitted information reaches 4–5 Mbytes. The amount of the transmitted results of assessing the state of the monitored objects in the DCS, which can be about 412 per one object, and the volume of each object – about 4 Kbytes – largely affect the bandwidth of communication channels. This accounts for the necessity to optimize the survey time for the monitored objects via minimizing the time for control over the DCS objects in real time. The problem is solved due to the method implemented in two stages: finding the shortest path and the shortest Hamiltonian cycle in a random graph describing the topology of the DCS communication channels. The proposed DCS-monitoring methods allow optimizing the survey time for the monitored objects in polynomial time and consequent improving the quality of performance and the quality of service provided to the DCS users in real time.